Firstlife - Showalter, Gena (Showalter, Gena. Everlife novels., 2016)
Locked in an asylum for her refusal to let her parents dictate her afterlife choices, Ten Lockwood finds herself caught in a violent power struggle between the two leading Everlife realms that would do anything to claim her powerful soul.